The results of microbiological methods of investigation of tuberculosis in Altay region - A. K. Strelis; N. V. Lukyanenko; L. V. Sultanov (Бюллетень сибирской медицины, 2003)
The qualitative and quantitative aspects of microbiological diagnosis of tuberculosis from 1996 to 2001 in Altay region are presented. In the process of realization of regional complex program «Fighting with tuberculosis» the positive dynamics of microscopy. The improvement of material technical basis of laboratory service, modern equipment, staff training helped in this process.